Himalayan Institutes' Network: Need for Resource Sharing - Singh, Anil; Prasad, R. C.; Gautam, J. N. (Journal of Information and Knowledge, 2002)
The paper suggests the need for networking of Himalayan Institutes' Libraries and Information Centres in the country for optimum resource sharing. The resource sharing and networking in libraries are the powerful tools both for increasing productivity and enhancing services to meet the chariging needs of library users. The proposed network ensures effective biblipgraphic control, document delivery, co-operative acquisition of serials and other literature in the field and dissemination of relevant information to the needy persons.